2005
DOI: 10.1016/j.cell.2005.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Fibroblasts Present in Invasive Human Breast Carcinomas Promote Tumor Growth and Angiogenesis through Elevated SDF-1/CXCL12 Secretion

Abstract: Fibroblasts often constitute the majority of the stromal cells within a breast carcinoma, yet the functional contributions of these cells to tumorigenesis are poorly understood. Using a coimplantation tumor xenograft model, we demonstrate that carcinoma-associated fibroblasts (CAFs) extracted from human breast carcinomas promote the growth of admixed breast carcinoma cells significantly more than do normal mammary fibroblasts derived from the same patients. The CAFs, which exhibit the traits of myofibroblasts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

95
2,959
8
32

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 3,292 publications
(3,144 citation statements)
references
References 53 publications
95
2,959
8
32
Order By: Relevance
“…The results from immunofluorescent (IF) staining ( Figure 1 a), Western blotting (WB, Figure 1b) and quantitative polymerase chain reaction (PCR) (Figure 1c) consistently suggested that treatment with TH for 48 h significantly stimulated the expression of α‐SMA and SDF‐1—two representative markers for CAFs—in primary mammary fibroblasts 29. The treatment also upregulated the levels of Type I and IV collagen, which are also highly expressed in CAF (Figure 1b and c).…”
Section: Resultsmentioning
confidence: 79%
“…The results from immunofluorescent (IF) staining ( Figure 1 a), Western blotting (WB, Figure 1b) and quantitative polymerase chain reaction (PCR) (Figure 1c) consistently suggested that treatment with TH for 48 h significantly stimulated the expression of α‐SMA and SDF‐1—two representative markers for CAFs—in primary mammary fibroblasts 29. The treatment also upregulated the levels of Type I and IV collagen, which are also highly expressed in CAF (Figure 1b and c).…”
Section: Resultsmentioning
confidence: 79%
“…Previous studies have reported that activated tumor fibroblasts or cancer‐associated fibroblasts are phenotypically and functionally different from normal fibroblasts (Zhang et al ., 2017). CAFs have been shown to stimulate cancer progression and proliferation through helping create the extracellular matrix (ECM) and through the secretion of a variety of cytokines, chemokines, and growth factors, such as vascular endothelial growth factor (VEGF), transforming growth factor‐β (TGF‐β), and fibroblast growth factor 2 (FGF2) (Kalluri, 2016; Kalluri and Zeisberg, 2006; Orimo et al ., 2005; Shen et al ., 2016). Accumulating evidence suggests that miRNAs play key roles in the activation and transition of fibroblasts (Aprelikova et al ., 2013; Mitra et al ., 2012).…”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…While often referred to generically as CAFs, there are evidently a number of distinctive fibroblastic cell types encompassed by this designation, including recruited myofibroblasts expressing smooth muscle actin, and activated (‘reactive’) resident tissue fibroblasts (Pietras and Ostman, 2010). The functionality of CAFs has been demonstrated for example by co‐injection of CAFs together with tumor cells, which enhances tumor growth by promoting ECM synthesis and stiffening, inducing angiogenesis, and recruiting growth‐promoting inflammatory cells such as macrophages (Erez et al., 2010; Kalluri and Zeisberg, 2006; Orimo et al., 2005; Tlsty and Coussens, 2006). CAFs are particularly abundant in certain human cancers, such as PDAC, and in various carcinomas at advanced stages of progression (e.g., breast and colorectal cancer).…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…The high interstitial pressure measured in the desmoplastic stroma limits tumor blood vessel perfusion and the delivery of chemo and other forms of therapy. Furthermore, CAFs may also mediate resistance to anti‐VEGF therapy, likely via their production of stromal‐cell derived factor‐1 (SDF1, or CXCL12) – a potent chemotactic signal for proangiogenic myeloid cells (Orimo et al., 2005) – or by directly stimulating angiogenesis via their secretion of platelet‐derived growth factor‐C (PDGF‐C) (Crawford et al., 2009) and basic fibroblast growth factor (FGF2) (Pietras et al., 2008). …”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%